Families and Collective Futures: Developing a Program Logic Model for Arts-Based Psychosocial Practice With South African Rural Communities - Havsteen-Franklin, Dominik; Swanepoel, Marlize; Jones, Jesika; Conradie, Uné (Frontiers in Psychology, 2021)
Aim This aim of this study is to describe the development of a professional-led programme logic model to guide arts-based psychosocial practice delivered in rural South African farming communities, including workers and their families affected by transgenerational traumas. Background The rationale for developing a programme logic model for arts-based psychosocial practice in South Africa was based on the lack of evidence for effective community arts-based psychosocial interventions for collective trauma, unknown consensus about best practices and the requirement to reconsider individualised psychosocial practices. Further to this, the aims and benefits of the practice required clarity given the psychosocial complexity of the environment within which the practices for this population are being offered. The logic model offers a valuable resource for practitioners, participants and funders to understand the problem being addressed, how practice is defined, as well as the impact of practice. Methods The authors used a systematic iterative approach to describe the operationalisation of arts-based psychosocial practice. This resulted in the design of the logic model being informed by data from the focus groups, literature overview and operational policies and organisational documents. The development of the logic model involved actively investigating with practitioners their work with remote farming communities. We used organisational documents, policies and an overview of the literature to identify the operational elements, a focus group and thematised personal constructs with practitioners to define salient practice elements and their relationship to perceived benefits and lastly feedback from practitioners following implementation to make adjustments to the logic model. Results The results were clearly identified in the form of visual mapping using the design of a programme logic model. The logic model was divided into 5 parts and was verified by practitioners following implementation as (Part 1) main presenting problem, (Part 2) operational processes, (Part 3) practice elements, (Part 4) benefits and impact and (Part 5) review.